EVALUATING THE IMPACT OF FINANCIAL LITERACY AND KEY FACTORS ON SMES’ FINTECH ADOPTION INTENTION - Ahsan, Arif; Yusuf, Dayang Hasliza Muhd; Zainol Abidin, Juraini; AbdulGhani, Mohd Rosli; Kamaruddin, Nur Syuhadah; Rozali, Ahmad Zulhusny (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2026)
The key focus of this study was to examine the impact of financial literacy as a moderating variable between perceived relative advantage and intention to adopt Fintech. In addition, the study investigated other key drivers of Fintech adoption, including perceived organizational readiness, perceived competitive pressure, perceived security, and facilitating conditions, and their influence on SMEs’ behavioural intention to adopt Fintech. A quantitative research design was employed under a positivist paradigm. Data was collected through a structured questionnaire based on a five‑point Likert scale. The unit of analysis comprised SME owners and senior managers in Dhaka city, Bangladesh. Using a purposive non‑probability sampling method, a total of 189 valid responses were obtained, which is considered adequate for structural equation modeling. Data were analyzed using PLS-SEM, which is particularly suitable for complex models and medium sample sizes. The questionnaire consisted of seven constructs: perceived organizational readiness, perceived relative advantage, perceived competitive pressure, perceived security, facilitating conditions, financial literacy, and behavioural intention to adopt Fintech. The results revealed that perceived organizational readiness, perceived relative advantage, perceived competitive pressure, and perceived security had a positive influence on intention to adopt Fintech. However, facilitating conditions showed no significant effect. Furthermore, financial literacy did not moderate the relationship between perceived relative advantage and behavioural intention to adopt Fintech. Most respondents had at least two years of experience in operating SMEs, which enabled them to evaluate cost–benefit advantages without relying heavily on prior financial knowledge. The findings suggest that while financial literacy is important, its moderating role may be limited in contexts where SME decision‑makers already possess practical business experience. This outcome highlights the need for future research to explore alternative moderating variables, such as government support or perceived regulatory backing, to better understand Fintech adoption dynamics among SMEs.